Design And Construction Of Soil Monitoring In Chili Farming Using Temperature, Ph And Humidity Sensors Based On Arduino Uno - Bertauli Br Simorangkir; Solly Aryza; Parlin Siagian (Sean Institute, 2025)
Modern agriculture is increasingly adopting technology to improve efficiency and productivity. This study proposes the development of a Multi-sensor-based Chili Plant Monitoring System integrated with Internet of Things (IoT) technology and accessed via a website. This study is designed to monitor important parameters such as temperature, soil moisture, and soil pH in real-time to improve the efficiency of agricultural management. This system uses a number of sensors placed around chili plants to measure environmental parameters accurately. The temperature sensor is used to monitor the temperature of the plant environment, while the soil moisture sensor monitors the level of soil moisture which is important for plant health. Thus, they can monitor the condition of their chili plants remotely and make more timely decisions. In addition, the system can provide automatic notifications to farmers via the website when environmental conditions reach a specified limit. For example, farmers can receive a notification if the temperature exceeds a threshold or if soil moisture drops below the desired level. This allows farmers to take preventive measures or make necessary adjustments quickly. This research makes an important contribution to the development of efficient and sustainable technology-based agriculture. The implementation of the Multi-sensor-Based Chili Plant Monitoring System accessed via this website allows farmers to better manage their agricultural land, increase yields, and optimize resource use.